Microgranulomas at Diagnosis Are Associated With Need for Antitumor Necrosis Factor Escalation in Pediatric Crohn Disease. Issue 5 (17th May 2022) - Moran, Christopher J.; Pankaj, Amaya; Kaplan, Jess L.; Deshpande, Vikram
ABSTRACT: Introduction: Granulomas are a pathologic hallmark of Crohn disease (CD) although they are found in only a subset of patients. Well-formed granulomas are associated with an aggressive phenotype although it is unknown if microgranulomas confer a similar phenotype. This study sought to define the incidence of microgranulomas in pediatric CD and compare the clinical course with cases with granulomas and those without granulomatous inflammation. Methods: We performed a single-center, retrospective study of pediatric CD patients who had at least 3 years of follow-up. initial diagnostic biopsies were systematically re-examined by a gastrointestinal pathologist. A priori definitions of granuloma (10+ histiocytes) and microgranuloma (4–9 histiocytes) were used. Disease outcomes of hospitalization, development of complicated disease behavior, perianal disease, and the use of anti-tumor necrosis factor (anti-TNF) therapy were assessed by Kaplan-Meier survival plots. Results: This study included 138 subjects with an average follow-up of 4.6 years. Granulomas were seen in 38 of 138 subjects (27.5%) and an additional 38 subjects (27.5%) had at least 1 microgranuloma (in the absence of granulomas). Escalation to anti-TNF therapy was higher in CD with granulomas ( P   =  0.001) and microgranulomas (P   =  0.0001) compared with those without granulomatous inflammation. Conclusions: A significant subset of pediatric CD patients have microgranulomas (in the absence of well-defined granulomas). Children with CD who have microgranulomas are escalated to anti-TNF therapy more frequently than those without granulomatous inflammation (and at a similar rate to those with granulomas). Pathologists should have a low threshold to report microgranulomas as they may help to predict disease behavior.